Characterization of Malassezia Furfur and its control by using plant extracts - Vijayakumar R; Muthukumar C; Kumar T; Saravanamuthu R (Wolters Kluwer Medknow Publications, 2006)
Malassezia furfur, a lipophilic, dimorphic and yeast-like fungus, occurring in human skin as an opportunistic pathogen, causes diseases such as dandruff, pityriasis versicolar, seborrheic dermatitis, etc. Suitable media for culturing the organism were standardized. A modified medium for the culturing of M. furfur has been proposed. Growth of the fungus was also determined in the presence of different carbon sources under the influence of different temperature, pH and salinity. Plant extracts of 19 species were screened against the growth of the fungus by using disc diffusion method and the results are discussed.